Industrial versus Laboratory Clinker Processing Using Grinding Aids (Scale Effect) - Joseph Jean Assaad (Advances in Materials Science and Engineering)
The evaluation of grinding aid (GA) effect on clinker processing in laboratory grinding mills is relatively simple. Yet, the results obtained cannot be directly transposed to industrial mills, given the fundamentally different operational modes and grinding parameters. This paper seeks to evaluate the scale effect by comparing the results obtained from a closed-circuit tube mill operating at 90 ton/hr to those determined using a 50-liter laboratory mill. Tests results have shown that the decrease in specific energy consumption (Ec) due to glycol or amine-based GA can be evaluated under laboratory conditions. However, such tests underestimate the actual performance that could be achieved in real-scale mills; the Ec reduction due to GA is around twofold higher when grinding is performed in real-scale mill. Compared to industrial tests, the cement particle size distribution curves widened and shifted towards higher diameters when grinding was performed under laboratory conditions, particularly with GA additions. This led to remarkable changes in water demand, setting time, and 1- and 28-day compressive strengths.